Medical biochemistry - Baynes, John W.; Dominiczak, Marek H. (Elsevier, 2022)
"Written by carefully selected global experts, practicing physicians, and educators in the various sub-disciplines of biochemistry, Medical Biochemistry, 6th Edition, offers a unique combination of research and clinical practice tailored to today's integrated courses. Covering clinically relevant topics in greater detail than other texts, this outstanding resource provides a strong overview of traditional areas in medical biochemistry along with state-of-the-art coverage of today's latest developments. You'll learn basic science concepts alongside clinical cases that describe patients likely to be encountered in clinical training, as well as how to use laboratory tests to diagnose and monitor the most important conditions. Thorough yet accessible, this clinically focused text is useful from medical school to clinical practice."--